Phenolic Content and Antioxidant Activity Water and Ethanol Extracts of Sungkai Leaves (Peronema canescens Jack) - Delima Engga Maretha; Dwi Fitri Yani; Lili Silvana; Mashuri Masri (UIN Sunan Gunung Djati Bandung, 2023)
Sungkai (Peronema canescens Jack) is a plant that has phenolic content as an antioxidant that can enhance the immune system (immunomodulator). This study aimed to determine the phenolic content and antioxidant activity of Sungkai leaves (Peronema canescens Jack). The method of antioxidant with invitro using of the DPPH where the ability of a compound to inhibit DPPH radicals is calculated from the absorbance value using UV-Vis spectroscopy. And Determination of total phenolic content was carried out using UV VIS spectroscopy at a wavelength of 745 nm with the help of Folin Ciocalteu reagentand a nd gallic acid standard curve . The test results showed that the water and ethanol extracts with a concentration of 0.1% had a phenolic content of 0.002% and 0.007%, their antioxidant activity (IC50) with a concentration of 0.02; 0.04; 0.06; 0.08; and 0.1% in the water and ethanol extracts of Sungkai leaves have values of 0.025% and 0.03% respectively. Therefore the best antioxidant activity (IC50) was extracts ethanol of sungkai leaves with phenolic content of 0.007% and IC50 of 0.03%.